STRATEGI PEMBELAJARAN DAN EFIKASI DIRI WARGA BELAJAR TERHADAP CAPAIAN BELAJAR - Muktiono Waspodo (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
Within non-formal context where a tutor plays an important role, this article discusses some instructional strategies and the learner’s self efficacy. After four learning principles are identified, learning achievement in non-formal education is defined. Having reviewed a number of instructional strategies, it elaborates the concept of self efficacy which covers performance experience, vicarious experience, verbal persuasion, and physiological state. Referring to some research reports, it concludes that there is positive causal relationship between efficacy and learning achievement. This article concludes that in selecting instructional strategies, the tutors should consider the learners’ efficacy and it gives the tutors and the supervisors a set of suggestions in relation to planning, organizing, and supervising the instructional process in the classroom.